NEED ANALYSIS IN CURRICULUM DEVELOPMENT OF ENGLISH SYLLABUS AT BANTEN JAYA UNIVERSITY - Dede Rohadi Fajri; Sisca Wulansari Saputri (Journal of English Language Teaching and Literature (JELTL), 2020)
The study used to be aimed at describing: (1) the goal needs of the students in learning English of Banten Jaya University, (2) the mastering needs of the students in mastering English of Banten Jaya University, and (3) the improvement at the teaching English syllabus. The topics of this study had been 152 students of the semester 1 of various departments of Banten Jaya University in the educational yr 2019/2020. The study consisted of data collection, data identiﬁcation, data quantiﬁcation, data description, and syllabus development. The English syllabus has been developed primarily based on the desires analysis data. The research instruments have been questionnaires and interview guides. The outcomes of the study are as follow. The goal needs of the students of Banten Jaya University in learning English are to enhance their English skills; the students’ proﬁciency is in the beginner level; studying English is useful for their subsequent career; the most popular subject matter; the center is photo illustration; the studying pastime is talking then reading comprehension; the trainer function is as a comments giver; the learners position is as energetic learners; and the setting is group work.